Strategi Penguatan Kelembagaan Bumdes Dalam Peningkatan Kesejahteraan Masyarakat Desa Sidoagung - Fathah, Rigel Nurul; Safitri, Teti Anggita; Saharuddin, Erni; Nindiasari, Avininda Dewi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This study aims to develop a strategic plan for the establishment of a Village-Owned Enterprise (BUMDes) in Sidoagung Village, Godean, Sleman, to improve community welfare. The research addresses the challenges faced by the village, such as the absence of a BUMDes, limited human resource capacity, and a lack of community participation in economic development. The method involves a series of assistance programs, including a workshop on potential mapping and business selection, training on institutional strengthening and governance, assistance in preparing the Articles of Association/Bylaws (AD/ART), and training on product innovation and marketing. The preliminary findings indicate that the BUMDes currently has minimal partnership networks, primarily limited to the sub-district level. It has also been identified that the BUMDes needs to expand its collaboration with various stakeholders, such as related government agencies, banks, and the private sector, to strengthen its position and accelerate business growth. Based on potential mapping, three business types were chosen: goat farming, catering, and field rental. These results highlight the need for structured assistance to formalize the BUMDes and enhance its managerial capacity.